Employment to Output Elasticities & Reforms towards Flexicurity: Evidence from OECD Countries - Holger Görg; Cecília Hornok; Catia Montagna; George E. Onwordi (Institute of Labor Economics (IZA), 2018)
How do labour market policies influence employment's responsiveness to output fluctuations (employment-output elasticity)? We revisit this question on a panel of OECD countries, which also incorporates the period of the Great Recession. We distinguish between passive and active labour market policies and allow for their interactions, i.e. the policy mix, to play a role. We find that the effects of any single policy change are shaped by the broader existing policy-mix within which it takes place. Finally, we evaluate the effect of a move to 'flexicurity' on the employment-output elasticity in each country.
Keywords: E24; E32; J21; J65; 330; employment-output elasticity; labour market policy; welfare state; flexicurity